WAKAF TUNAI DALAM PERSPEKTIF HUKUM ISLAM - M. Wahib Aziz (International Journal Ihya' 'Ulum al-Din, 2017)
For a long time, Muslims have been accustomed to donating with immovable objects, such as land and buildings. Those who can enjoy and utilize the land and building of wakaf is a community that is domiciled in the location around the wakaf property. Therefore, the idea of wakaf with money arises as it goes along with the need for funds to alleviate poverty while the location of the needy communities is spread outside the wakif area. Money is more flexible and does not recognize the boundaries of the distribution area. Cash wakaf is usually in the form of cash given by the wakif to the needy parties through the hands of amil zakat institution, infak and alms. This paper examines the extent to which the potential of cash wakaf, especially in Indonesia. In addition, to get a more in-depth review of the law of cash wakaf in the view of Islam and also to get the right formula in optimizing the prospect of cash wakaf, of which with directed to productive wakaf.---Sejak lama, umat Islam terbiasa berwakaf dengan benda tidak bergerak, yaitu berupa tanah dan bangunan. Pihak yang dapat menikmati dan memanfaatkan harta wakaf tanah dan bangunan itu adalah masyarakat yang berdomisili di lokasi sekitar harta wakaf tersebut berada. Seiring dengan kebutuhan dana untuk pengentasan kemiskinan yang sangat besar dan lokasinya yang tersebar di luar daerah para wakif, maka muncullah pemikiran untuk berwakaf dengan uang. Uang bersifat lebih fleksibel dan tidak mengenal batas wilayah pendistribusian. Wakaf tunai biasanya berupa uang tunai yang diberikan oleh pewakaf kepada yang berhak menerimanya melalui tangan lembaga amil zakat, infak dan sedekah atau bisa juga dengan surat berharga seperti cek. Tulisan ini mengkaji sejauh mana potensi wakaf tunai, terutama di Indonesia. Selain itu juga untuk mendapatkan kajian lebih mendalam tentang hukum wakaf tunai dalam pandangan Islam dan juga untuk mendapatkan formula yang tepat dalam mengoptimalkan prospek cerah wakaf tunai, di antaranya dengan diarahkan ke wakaf produktif.